The right to life: the moments of origin and loss - O. I. Amelchakov (Правоприменение)
The subject of the article is the right to life interpretation issue, as well as the definition of the term "life" applicable in the legal field, the study of the problems of establishing of the constitutional right to life realization moment and its loss. This is necessary due to the formalized nature of law and the unification of the legal categorical apparatus, controversy in the scientific community, as well as the lack of a holistic understanding of the moments of its origin and loss, which will improve modern legislation in the field of protecting the right to life, eliminate existing contradictions.The purpose of the study is to confirm or refute the author's hypothesis about the moment of the emergence of the right to life and its termination as processes interrelated with the context and society. The author interests how this moment is fixed in current Russian legislation as well as in international legal norms and the constitutions of some foreign countries.The methodology. The following general scientific and special methods of cognition were used in the work: dialectical, systemic, historical, comparison, analysis and synthesis, formal legal and statistical methods. The method of comparison was used in the analysis of the texts of constitutions in order to consolidate the moments of the emergence and loss of the right to human life. The formal legal method made it possible to identify contradictions in the legislation of Russia in terms of issues related to the emergence and loss of the right to life. The use of these methods in combination with the latest achievements made it possible to identify and analyze the content, essence and features of the emergence and loss of the human right to life in the Russian Federation and foreign states.The main results, scope of application. Within the framework of the scientific and practical problem the author considers various approaches to the right to life emergence and loss moments, identifies the main problems of the current legislation of Russia and compares it with international legal norms and the constitutions of some foreign countries in order to fix the right to life emergence and loss the moments.Conclusions. The moment of the occurrence of the right to life must be recognized as a birth of viable infant, and the moment of loss of the right to life – the onset of his death. The right to life of a premature newborn, including those with extremely low body weight, as well as those with certain complications, is realized by providing him with full medical care.